(untitled) (Journal of Fatima Jinnah Medical University, 2021)
Background: Parkinson’s disease is one of the most common neurodegenerative disease characterized by tremors at rest, rigidity and akinesia. Despite being one of the common neurodegenerative diseases etiology and progression of PD is complex and poorly understood and has proposed to be a combination of genetic and environmental factors. Nearly 80% of the patients of Parkinson’s disease go on to develop dementia. However, there are considerable variations in disease course and some patients develop dementia quite early in the disease course. The genetic factors and association of family history for early development of dementia is still something that is controversial and under study. This study is an attempt to understand the significance of family history in development of dementia in Parkinson’s disease. Patients and methods: This cross-sectional comparative study was conducted in Sheikh Zayed Postgraduate Medical Institute Lahore in which participants were assessed for dementia through Mini mental state examination. The subjects were divided in three groups of 30 each - Parkinson’s disease with dementia group, Parkinson’s disease without dementia group and a healthy control group and a potential association between family history of dementia and development of dementia in Parkinson’s disease was studied. Results: Out of total 90 patients, 23 (25.6%) had a family history of Parkinson’s disease in Group A (Parkinson’s disease with dementia), 9 (30.0%) patients in Group B (Parkinson’s disease without dementia) whereas in healthy controls only 5 (16.7%) patients had family history of Parkinson’s disease. Chi-square test revealed that the difference in the proportion of family history of Parkinson’s disease among the groups was insignificant (p-value = 0.393). Conclusion: No associations between dementia in PD and familial occurrence of dementia could be established. A longitudinal cohort study performing cross sections at intervals would be valuable to further study the effect of family history and early signs of dementia in patients of Parkinson’s disease.